Building the niche: the role of the S100 proteins in metastatic growth - Lukanidin, Eugene; Sleeman, Jonathan P. (Seminars in cancer biology, 2012)
Communication between cancer cells and stromal cells, often mediated by extracellular molecules in the tumor microenvironment, plays a central role in tumorigenesis and metastasis. The establishment of a pro-inflammatory milieu is increasingly recognized as an important consequence of these interactions. The family of S100 Ca2+-binding proteins has been implicated in many aspects of the interaction between cancer cells and stromal cells, and contributes to the formation of an inflammatory tumor microenvironment. Focusing on S100A4, S100A8 and S100A9, in this review we discuss the role these proteins play in primary tumors and in the development of metastases, in particular during the formation of pre-metastatic niches.
Available online 21 February 2012
Gesehen am 22.06.2018